Peningkatan Hasil Belajar Fisika Melalui Penerapan Media Pembelajaran E-Learning Berbasis Schoology: Studi Kasus di SMAN 1 Karangdowo. - Sugiarto, Toto (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2020)
The purpose of this research was to find out the Influence of E-Learning with Schoology on physics learning. The success indicators in this study is cosidered when at least 75% of students were able to passed the required standard minimum score. The reseach aims to evaluate the effectiveness of E-learning schoology to increase the level of understanding in learning physics at Karangdowo 1 Senior Highschool (SMAN 1 Karangdowo). The research was built upon the classroom observation to 35 students from the class of XI IPS 4. The research will begin on July 16 until August 20, 2019. The duplicated data containing three meeting on each cycle were recodered at two observational points: pre- and post-application cycles of the learning strategy. The students learning ability meassured by pre-cycle posttest was estabished as an initial baseline., following by recorded the improvement of the latter after the E-learning schoology has been applied. The result have shown that students understanding level in learning pysics is increased by 10.71% depicted by the increasing number of students (in percentage) that passed the standard minimum grade 70, on pre-cycle (25.7%) compared with the post-cyle (51.4 and 85.71%). The latter two scores were obtained from the post cycle-posttest scores after the application of the basic E-learning schoology and its associated modification method, respectively.Therefore, it can be concluded that the E-learning schoology can be considered as a promising method to increase learning outcomes for senior high school students in learning physics.